Evaluating Job Satisfaction and Family Life Satisfaction amid Organizational Role Stress among Executives: A Comprehensive Approach - Kaur, Gagandeep; Virk, Sukhmani (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted from April to December, 2023 at Agro-based industries of Punjab, India namely, Textile Industry and Food & Beverage Industry to study job satisfaction and family life satisfaction amid organisational role stress among the middle level and lower-level managers. The study explored the various factors contributing towards job satisfaction and family life satisfaction amongst executives working in the agro-based industry of Punjab, specifically the textile industry and food & beverage industry. The primary data for this study was collected from a total sample of 300 middle- and lower-level executives operating in 30 units of agro based industry particularly the textile industry and food & beverage industry. The analysis revealed five major factors contributing to job dissatisfaction and four factors contributing to family life satisfaction among the executives. The factors responsible for job dissatisfaction as per the responses of the managers were Continuous motivation; Favourable policies; Healthy workplace relations; Employee-centric work environment and Grievance handling. Similarly, the factors for family life satisfaction were Work-life balance; Financial stability; Residential location satisfaction and Interpersonal relationships. The results provided insights for organizational management and policy makers on how to improve employee satisfaction by addressing the elements that were linked to job dissatisfaction by emphasising that creating a motivated workforce and lowering stress levels at work can lead to better productivity and general employee well-being.